Islamic estate planning: factors influencing wills (wasiyyah) adoption among muslim community in Papar, Sabah / Munirah Ismail - Ismail, Munirah (2018)
The problem to be addressed in this study is that there has been an increasingamount of unclaimed property or frozen property in Malaysia. Where the increase occurs every year and involves an excessive amount. According to Prof. Datin Dr.Azizan Baharuddin during the seminar of "Faraid and will planning: The issue offrozen estate and its settlement in Malaysia" on 29 Mac 2016, the value of assets not claimed by the heirs in this country is increasing from year to year. In 2006, there was estimated that a million claims of heritage worth RM38 billion still frozen, the figure then increased to RM40 billion in 2009 and RM12 billion in 2011. Also, according toher, the lack of awareness of the importance of the will of planning is among the main factors that cause the assets of Muslims to be unclaimed and frozen in the country.Thereport in 2012 showed that the amount is RM45 billion and this shocking statistic are predicted to increase every year. The increase in statistics that occur each year indicates that this problem needs to be resolved immediately. In 2016, the amount of unclaimed inheritance increase to RM60 Billion An interview conducted by Khalid Abdi Nur in early 2011 with the management of Amanah Raya Berhad confirmed that this scenario has not changed. A possible reason of this has been identified that most Muslims in Malaysia do not view estate planning such as wills, waqf and grant seriously, in which they rely only on faraid in the distribution of inheritance hence previous research proved that some of them are unsure about making a will. So, basedon the problem, the objectives of this study are to examine the factors that influence wills adoption among Muslims in Malaysia. The specific objectives are first, to determine the relationship between knowledge and wills adoption among Muslims in Malaysia. Second objective is, to examine the relationship between life events and wills adoption. Third objective is, to examine the relationship between organizations and wills adoption.This research is a quantitative study which has been used a primary data collection through the individual questionnaire to examine factors influence willsadoption among Muslims. The method used in this study is descriptive, reliability, and correlation. Based on this study, it is found that there is a relationship between knowledge and organization with wills adoption although the relationship is weak.These factors are found to be related to the wills adoption because the factors such as knowledge can help the respondents to understand the importance of adopting thewills. While organizational factors are proven to have a relationship with the wills adoption, based on the questionnaire distributed to respondent it shows that if the organization has a good service quality level, well known and others, it can be a factor in wills adoption. It is, therefore, understandable that knowledge and organization play an important role in increasing the wills adoption because the higher the knowledge of a person about wills, will increases their desire to adopt the wills as well as the organization. In addition, from this study, it is also found that there is no relationship between life events and wills adoption. This is because this factor is not the cause of respondents in this study to adopt a will.